‘Against the pain of the slepe splene¨: errors and corrections in the manuscript copies of The Secrets of Alexis of Piedemont and a Niewe Herball or Historie of Plants - Lorente-Sánchez, Juan (Universidad de Almería, 2025)
The present paper analyses the scribal errors and corrections in two treatises held in Glasgow University Library, MS Ferguson 7, which are, up until the present-day, the only known manuscript copies of the Early Modern English printed scientific compositions entitled The Secrets of Alexis of Piedmont and A Niewe Herball or Historie of Plants. The study aims to account for any variation between the pieces, as well as to evaluate the degree of scribal carefulness in carrying out an appropriate copying process. It thus endeavours to shed some new light on the likely value of the treatises and the intended purposes of their reproduction in the manuscript.
Keywords: Lengua inglesa - Errores de uso; Scribal Errors and Corrections; Manuscript Copies; Early Modern English; The Secrets of Alexis of Piedmont; A Niewe Herball or Historie of Plants